Organokines and liver enzymes in adolescent girls with polycystic ovary syndrome during randomized treatments - Garcia-Beltran, Cristina; Peyrou, Marion; Navarro-Gascon, Artur; López-Bermejo, Abel; de Zegher, Francis; Villarroya, Francesc; Ibáñez, Lourdes (Frontiers in Endocrinology, 2024)
Introduction Polycystic ovary syndrome (PCOS) is often associated with metabolic-associated fatty liver disease (MAFLD). MAFLD has been associated with altered hepatic function, systemic dysmetabolism, and abnormal circulating levels of signaling molecules called organokines. Here, we assessed the effects of two randomized treatments on a set of organokines in adolescent girls with PCOS and without obesity, and report the associations with circulating biomarkers of liver damage, which were assessed longitudinally in the aforementioned studies as safety markers. Materials and methods Liver enzymes [aspartate aminotransferase (AST), alanine aminotransferase (ALT), and gamma-glutamyl transferase (GGT)] were assessed as safety markers in previous randomized pilot studies comparing the effects of an oral contraceptive (OC) with those of a low-dose combination of spironolactone-pioglitazone-metformin (spiomet) for 1 year. As a post hoc endpoint, the organokines fibroblast growth factor-21 (FGF21), diazepam-binding protein-1 (DBI), and meteorin-like protein (METRNL) were assessed by ELISA after 6 months of OC (N = 26) or spiomet (N = 28). Auxological, endocrine-metabolic, body composition (using DXA), and abdominal fat partitioning (using MRI) were also evaluated. Healthy, age-matched adolescent girls (N = 17) served as controls. Results Circulating ALT and GGT levels increased during OC treatment and returned to baseline concentrations in the post-treatment phase; in contrast, spiomet treatment elicited no detectable changes in ALT and GGT concentrations. In relation to organokines after 6 months of treatment, (1) FGF21 levels were significantly higher in PCOS adolescents than in control girls; (2) DBI levels were lower in OC-treated girls than in controls and spiomet-treated girls; and (3) no differences were observed in METRNL concentrations between PCOS girls and controls. Serum ALT and GGT levels were directly correlated with circulating METRNL levels only in OC-treated girls (R = 0.449, P = 0.036 and R = 0.552, P = 0.004, respectively). Conclusion The on-treatment increase in ALT and GGT levels occurring only in OC-treated girls is associated with circulating METRNL levels, suggesting enhanced METRNL synthesis as a reaction to the hepatic changes elicited by OC treatment. Clinical Trial Registration https://doi.org, identifiers 10.1186/ISRCTN29234515, 10.1186/ISRCTN11062950.